DNA sequence requirements for replication fork arrest at terC in Bacillus subtilis. - Smith, M T (1988)
The replication terminus, terC, of Bacillus subtilis is the chromosomal site at which movement of the clockwise replication fork is blocked. The effect of deletion or modification of DNA sequences on either side of terC (defined by the sequence location of the arrested clockwise fork junction) has been investigated. Deletion of sequences ahead of terC to within 250 base pairs (bp) had no effect on fork arrest, whereas removal of a further 130 bp abolished it. The 250-bp segment immediately ahead of terC encompassed the previously identified inverted repeat region as well as potential promoters for the transcription of an adjoining open reading frame (ORF). Deletion of DNA from the other side of terC up to 80 bp from it also abolished fork arrest. This deletion removed the bulk of the ORF. Disruption of this ORF by the insertion of 4 bp also abolished fork arrest. A model for clockwise fork arrest at terC, implicating both the inverted repeat region and the protein product of the ORF, is proposed.